Literature Study : Implementation of Business Ethics and Good Corporate Governance Practices in Improving Financial Perfomance - Mita, Vina Yulia; Trisnaningsih, Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study analyzes the role of business ethics and Good Corporate Governance (GCG) in improving the financial performance of PT. Waskita Karya, focusing on a corruption case involving the company's president director. Using a literature study method, the research evaluates empirical evidence from relevant studies. The findings highlight that implementing strong business ethics and effective GCG—encompassing transparency, accountability, responsibility, independence, and fairness—enhances financial performance. These principles support better management decisions, conflict prevention, and healthier financial outcomes. Thus, business ethics and GCG are crucial in bolstering corporate image and financial success.